1982
DOI: 10.1152/jn.1982.48.6.1302
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological properties of neocortical neurons in vitro

Abstract: 1. Intracellular recordings were obtained from neurons of the guinea pig sensorimotor cortical slice maintained in vitro. Under control recording conditions input resistances, time constants, and spiking characteristics of slice neurons were well within the ranges reported by other investigators for neocortical neurons in situ. However, resting potentials (mean of -75 mV) and spike amplitudes (mean of 93.5 mV) were 10-25 mV greater than has been observed in intact preparations. 2. Current-voltage relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
446
5
15

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 888 publications
(525 citation statements)
references
References 0 publications
59
446
5
15
Order By: Relevance
“…The late EPSPs reported here by afferent stimulation in slices taken from developmentally mature rats (ie 6-8 weeks; Zhu, 2000) resemble the late EPSPs evoked in layer II/III frontal cortical pyramidal neurons by intracortical stimulation in slices from young prepubertal rats (o6 weeks; 120-150 g; Sutor and Hablitz, 1989) or in guinea-pig neocortical neurons that were characterized as stimulus intensity sensitive (Connors et al, 1982), as similarly reported here (see Figure 8). These neurons, which were mostly recovered in cortical deep layer V following intracellular recording/ labeling, had axons which ramified extensively and ascended to superficial layers, in addition to giving off several secondary axons that target subcortical structures (see Figure 1c).…”
Section: Discussionsupporting
confidence: 81%
“…The late EPSPs reported here by afferent stimulation in slices taken from developmentally mature rats (ie 6-8 weeks; Zhu, 2000) resemble the late EPSPs evoked in layer II/III frontal cortical pyramidal neurons by intracortical stimulation in slices from young prepubertal rats (o6 weeks; 120-150 g; Sutor and Hablitz, 1989) or in guinea-pig neocortical neurons that were characterized as stimulus intensity sensitive (Connors et al, 1982), as similarly reported here (see Figure 8). These neurons, which were mostly recovered in cortical deep layer V following intracellular recording/ labeling, had axons which ramified extensively and ascended to superficial layers, in addition to giving off several secondary axons that target subcortical structures (see Figure 1c).…”
Section: Discussionsupporting
confidence: 81%
“…The network model consists of two homogeneous populations of neurons, one excitatory (E), displaying adaptation, and the other one inhibitory (I), without adaptation. This is a reasonable assumption, for example, for cortical neurons, since experimental studies report that in the cortex most of the inhibitory neurons do not display spike adaptation [3], [4], [14].…”
Section: 11mentioning
confidence: 97%
“…1A-C) that had resting potentials _ 60 mV and APs ranging between 55 and 80 mV (n=82). All but two of the morphologically-identified cells (n=42) were regular spiking 6,45 pyramidal neurons ( Figs 1D, 2A-B) whose somata were located in the infragranular (n=24) or supragranular layers (n=16), 1 to 2 mm from the cortical stimulating electrode array (Fig. 1A-B).…”
Section: Database and Morphological Features Of Recorded Neuronsmentioning
confidence: 99%